Effect of Various Parameters on Finishing of Inner Surfaces of Brass Tubes Using Magnetic Abrasive by RSM: A Study - Grewal, Harinder Singh; Singh, Avtar; Singh, Jaiinder Preet (Asian Review of Mechanical Engineering, 2015)
With the increase of technology and the demand of industry the surface finish requirements are also increasing. Conventional echnologies like grinding and lapping etc. fail to finish some pieces such as pipes, complex shape tubes consisting of straight and bent sections up to desired accuracy. Magnetic Abrasive Finishing (MAF) is one of the a dvanced finishing methods, proposed to produce highly finished surfaces of brass340 pipes. In this research work the process, finishing characteristics and the principle of magnetic abrasive finishing of pipes using sintered magnetic abrasives are described. The sintered based of Al2O3 magnetic abrasives with iron particle of size 106 μm were used in this work. The Statistically designed experiments based on Taguchi methods show that weight of abrasive, Revolutions per minute (rpm), finishing time and type of lubricant which have significant effect on the surface roughness obtained. The effects of lubricants on surface finish are also analyzed in this work by using different types of lubricants. It is noticed that the surface finish was affected by the change of type of lubricant and the internal surface finish of pipes were analyzed in terms of percent improvement in surface finish (PISF) and using Response Surface Methodology (RSM). The obtained maximum PISF was 60% by using toothpaste as a lubricant and minimum surface r oughness w as 0 .126 μ m R a. T he improvement in surface finish was further validated using RRay Diffraction (XRD) technique.